Jurnal Ilmiah: Pengaruh Salat Terhadap Kesejahteraan Mental dan Spiritual Komunitas Muslim di Jambi - Alisya, Sri Ratu; Rahmawati, Ririn; Ramadhan, M. Razinsyah; Maulana, Riska; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Prayer, or prayer, is a ritual worship of Muslims that is carried out by standing, bowing, prostrating, and sitting with tuma'ninah and is done at certain times. This study aims to examine the impact of prayer on the spiritual and psychological well-being of Muslims. Prayer, as a core worship in Islam, is believed to have great potential in shaping character, inner peace, and transcendental relationship with God. Through a qualitative and quantitative approach, the study will explore individuals' perceptions of prayer practices, their experiences during and after prayer, and their correlation with stress levels, anxiety, and life satisfaction. The results of the study are expected to provide a comprehensive understanding of the role of prayer in improving the quality of life of Muslims and become the basis for spiritual-based interventions for mental health.